Correlation of Greenhouse Gas Emissions with Economic Growth in the European Union (2010-2019) - Laszlo, Torok (International Journal of Energy Economics and Policy, 2023)
A prominent research area in energy economics is the study of the correlation between economic growth and CO2 emissions. Using the combined application of correlation calculation and cluster analysis based on empirical data, the study typifies and arranges the EU member states into homogeneous groups based on the pattern of the two variables moving together based on data from the period 2010-2019. This methodology allows a test of the "decoupling" theory that can be used to describe the interaction between environmental pressures and economic development. The results can be used to infer the status of clustered Member States in the decoupling process. The results are ambivalent across member countries. For several EU Member States, different degrees of decoupling can be observed, i.e. GDP growth has been accompanied by a reduction of the ecological footprint in those countries. However, there are also member countries where the decoupling did not work, because the reduction of CO2 emissions was accompanied by a decrease in GDP.